Pengaruh Inokulan Blue-green Algae dan Pupuk N terhadap Populasi BGA, Kandungan N-total tanah, Serapan N, Konsentrasi N dan Berat Kering Tanaman Padi (Oryza sativa L.) pada Inceptisols Asal Jatinangor - Mieke Rochimi Setiawati (Soilrens, 2014)
This study aims to determine the effect of the combination of BGA inoculant and N fertilizer on total-N of the soil, N uptake, N concentration and dry weight of paddy rice (Oryza sativa L.) in Inceptisols Jatinangor. This research was conducted in the green house of the Faculty of Agriculture, University of Padjadjaran, Jatinangor, Sumedang. The study used a randomized block design (RAK) factorial, with two treatment factors, namely N fertilizer (N) 4 levels of factors, namely; n1 = 0.326 g pot-1 urea, urea n2 = 0.652 g pot-1, n3 = 0.978 g pot-1 urea and urea n4 = 1.304 g pot-1. The second factor is the BGA inoculants (B) which consists of 3 levels of factors, namely; b0 = no inoculant BGA, b1 = 0.025 g inoculant BGA pot-1 and b2 = 0.05 g pot-1 inoculant BGA each repeated 3 times. The results showed there was an interaction between N fertilizer with Blue-green Algae inoculant on the increasing in dry weight of the canopy, but not the total-N content of the soil, N uptake, and N concentration of rice plants. N fertilizer and Blue-green algae inoculants affected the increaseing on total-N soil. Based on the increasing in dry weight of rice plant canopy, BGA inoculant application can save the use of fertilizer N half of a given dose of urea fertilizer